Association between hemoglobin glycation index and mortality in critically ill patients: a retrospective cohort study - Liwei Pan; Fengfeng Lu; Bihuan Cheng; Wenwu Zhang; Benji Wang (Journal of Health, Population and Nutrition)
Abstract Background Glycemic variability is increasingly recognized as a critical factor influencing outcomes in intensive care, yet its prognostic role remains unclear. The Hemoglobin Glycation Index (HGI), which reflects individual glycemic variation, has not been thoroughly studied in critically ill populations. Aim To evaluate the association between HGI and all-cause mortality in critically ill patients using data from a large intensive care unit (ICU) cohort. Methods We conducted a retrospective cohort study using the MIMIC-IV database. The primary outcomes were 30-, 90-, and 365-day all-cause mortality; in-hospital mortality was secondary. Kaplan-Meier analysis, Cox regression, and restricted cubic spline (RCS) modeling were used to assess mortality risk across HGI levels. Propensity score matching (PSM) and subgroup analyses were performed to ensure robustness. Results Among 9,695 patients, those with low HGI (< − 0.40) had significantly higher mortality (P < 0.001). RCS analysis showed a nonlinear association between HGI and 30-day mortality. Higher HGI values were independently associated with reduced risk of death at all time points, with hazard ratios ranging from 0.43 to 0.76 (P < 0.001). These associations persisted after multivariable adjustment and PSM. Subgroup analyses showed consistent results across patient characteristics. Conclusions Lower HGI values are associated with increased short- and long-term mortality in critically ill patients. HGI may serve as a valuable prognostic biomarker for risk stratification in ICU settings.